ANALISIS KERUSAKAN PERMUKAAN JALAN DENGAN METODE PAVEMENT CONDITION INDEX DAN PEMETAAN BERDASARKAN SISTEM INFORMASI GEOGRAFI (STUDI KASUS: JALAN RAYA KEBONAGUNG - JALAN RAYA GENENGAN) - Randhita Bintang Wijaya; Hendrata Wibisana (LPPM Universitas Abdurrab, 2024)
Damaged roads, if follow-up repairs are not carried out immediately, cause greater damage and require greater costs to repair, so efforts need to be made to maintain the condition of the road to avoid this. So this research aims to find an index of the level of damage to the road pavement on the Malang - Kepanjen arterial road section with the help of civil engineering using the Pavement Condition Index (PCI) method and mapping of the condition of road damage in the research area using the help of the Geographic Information System (GIS) will be carried out. Based on the results of the analysis and calculations, the condition of road surface damage was obtained, namely, shoving, rutting, depression, patches, holes, alligator cracks, longitudinal cracks, edge cracks, and block cracks. Meanwhile, the Pavement Condition Index (PCI) value for each road, namely the Kebonagung highway has a PCI value of 76.8 (Very Good) and the Genengan highway has a PCI value of 80.75 (Very Good). After obtaining all the damage values based on the Pavement Condition Index (PCI) method, the Geographic Information System was implemented, namely creating a thematic map of the road damage values on each road in the research location so that the mapping of the road damage values could be used as a reference to see the condition of the roads in the Pakisaji and Kepanjen sub-district.